The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5ra00587f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular engineering of quinoxaline dyes toward more efficient sensitizers for dye-sensitized solar cells

Abstract: N-annulated perylene-containing quinoxaline sensitizer (NIQ4) displays remarkable performance in light harvesting, electron injection, and dye regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 79 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…In particular the diphenylquinoxaline unit has shown a great potential in anti-aggregation and broadening spectra response. 141 The recent developments of quinoxaline derivatives for photovoltaic have been recently reviewed [142][143][144] and structures presented in these reviews will not be discussed here.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In particular the diphenylquinoxaline unit has shown a great potential in anti-aggregation and broadening spectra response. 141 The recent developments of quinoxaline derivatives for photovoltaic have been recently reviewed [142][143][144] and structures presented in these reviews will not be discussed here.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A literature search revealed that quinoxaline derivatives have been employed for various applications such as organic photovoltaics, organic light emitting diodes (OLEDs) and dye sensitized solar cells, etc. [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing efforts to optimize solar energy conversion are frequently inspired by Nature, which uses finely tuned assemblies of chromophores to harness sunlight. , In photosynthetic organisms, light-harvesting complexes of chlorophyll and bacteriochlorophyll derivatives are optimized to collect and funnel solar energy to reaction centers where charge separation takes place. TiO 2 -based dye-sensitized solar cells (DSSCs), on the other hand, depend on adsorbed dyes which perform both the light-harvesting and interfacial charge-separation steps. Although self-assembly of dyes on the metal oxide surface is prevalent owing to their high surface density, , aggregation of dyes on TiO 2 is frequently reported to lower the rate and yield of electron injection, resulting in lower photocurrents. Consequently, high-performing DSSCs often employ spacer molecules, competitively binding molecules such as organophosphates, functionalized dyes with steric hindrance, or surface treatments to prevent dye aggregation. The reduced photocurrents that result from sensitizer aggregation are variously attributed to decreased excited-state lifetime, self-quenching, attenuation of light by a thicker dye layer, and weak electronic coupling of dyes to TiO 2 as a result of greater distance from the surface.…”
Section: Introductionmentioning
confidence: 99%